The Effect of Hypnobirthing Relaxation on Reducing Anxiety Levels in Pregnant Women Trimester III - Handayani, Yuni; Anggraeni , Ernawati; Kustin, Kustin; Fauzi , Fivie Faronita (Universitas Islam Jember, 2024)
Anxiety is a common mental disorder of unknown cause, characterized by extreme feelings of fear or worry. The impact of untreated anxiety on the mother can be tuberculosis, preeclampsia, and postpartum depression, while in infants, there can be Low Birth Weight, prematurity, and stunting. The solution that can be done is with non-pharmacological methods, namely hypnobirthing. This method can help mothers overcome fear to undergo a safe and healthy pregnancy. The purpose of this study was to determine the level of anxiety before being given hypnobirthing relaxation, the level of anxiety after being given hypnobirthing relaxation, and the effect of hypnobirthing relaxation and whether hypnobirthing relaxation can reduce anxiety in third-trimester pregnant women. This research method uses a pre-experiment design with a one-group pretest and posttest design. The population in the study was 47 pregnant women, with the acquisition of 32 samples with purposive sampling that entered the inclusion criteria. The results obtained p-value = 0.001 ≤ α = 0.05, which means there is an effect of giving hypnobirthing relaxation on reducing anxiety levels in third-trimester pregnant women in Plerean Village, Sumberjambe District, with a decrease of 30.469. Conclusion Hypnobirthing relaxation helps reduce anxiety in pregnant women so it can be concluded that there is a huge difference in anxiety levels before and after hypnobirthing relaxation is given.